Investigation of a genetic association of a class III skeletal pattern - Tunasoylu Begüm; Ünüvar Yazgı Ay; Erdoğdu İbrahim Halil (Sciendo, 2022)
The present study investigated the association between the human growth hormone receptor (GHR) and collagen type II alpha 1 chain (COL2A1) gene polymorphism of malocclusions in patients presenting with a maxillary retrognathic-related Class III skeletal pattern and a mandibular prognathic-related Class III skeletal pattern.